Influencer-driven mercantilism : unveiling the role of social proof in consumer behavior with women regarding beauty standards - Kristel Eir Eiríksdóttir 1999- (2024)
Self-esteem and body image correlate. When it comes to women's self-esteem, it plays a role in the perception of their beauty standards that are shaped by influencers and social media. The significant factors are the influencers that consumers follow and the time spent on social media platforms. According to previous studies, influencers shape consumer preferences and beauty standards. Moreover, the key terms, social proof, and social comparison influence consumer behavior. Research highlights the power of influencers to shape beauty standards and consumer preferences and choices. A total of 153 Icelandic women participated in the study. Linear regression was performed three times, where dependent variables were self-esteem, body image, and consumerism. This study uncovered a notable trend: Individuals with heavier weight or higher BMI tended to have lower self-esteem and were more inclined to engage with social media and influencers. This pattern reflects the influence of social comparison and social proof tactics employed by influencers on their platforms. It was concluded that beauty standards, self-esteem, and influencers are the main contributing factors to consumer behavior among Iceland women. Keywords: Self-esteem, beauty standards, social media, influencers, social proof, social comparison Sjálfsálit og líkamsímynd hafa fylgni. Sjálfsálit kvenna markaðst að fegurðarviðmiði þeirra sem hafa mótast af áhrifavöldum og samfélagsmiðlum. Mikilvægir þættir eru áhrifavaldarnir sem neytendur fylgja og tíminn sem varið er á samfélagsmiðlum. Samkvæmt rannsóknum móta áhrifavaldar neytendur og fegurð viðmiði samfélagsins. Þar að auki höfðu lykilhugtökin, félagsleg sönnun og félagslegur samanburður áhrif á hegðun neytenda. Þessi rannsókn leggur áherslu á kraft áhrifavalda til að móta fegurðarstaðla, neysluhyggju og val neytenda. Alls tóku 153 íslenskar konur þátt í rannsókninni. Línuleg aðhvarfsgreining var framkvæmd þrisvar sinnum þar sem frumbreytur voru sjálfsálit, líkamsímynd og neysluhyggja. Þessi rannsókn ...